INTRAMOLECULAR CYCLIZATION REACTION OF AMIDO-UREIDO (OR THIOUREIDO)-ACETALS - LEE, YS; KIM, CS; PARK, H (ELSEVIER SCIENCE BV, 1994)
Intramolecular cyclization reaction of the compound having amide, urea and acetal functional groups was investigated under various conditions. In acidic conditions, the cyclization reaction of N-methyl-N'-(2,2-dimethoxyethyl)-N'-(alkyl- or phenylcarbamoyl)glycine amide proceeded only to afford imidazolinone derivative via an acyliminium ion intermediate formed by intramolecular amidoalkylation reaction of amide and acetal functional groups. However, the corresponding compounds having thiourea functional group resulted in the formation of iminothiazolidine derivatives as major product and pyrazinone compounds as minor product. In nearly neutral or basic conditions, both of ureido- or thioureidoacetals afforded hydantoin or thiohydantoin derivatives, respectively, in excellent yield.